Literasi Media Sosial Humas Pemerintah Daerah - Putra, Novian Anata (Universitas Negeri Yogyakarta, 2017)
Nowadays, the government is trying to fight against hoax. One of them, PresidentJoko Widodo instructed to improve the function of government public relations andinformation managers to ward off hoaxes spread quickly in social media. However, itwill work if government public relations officers have adequate social media literacyskills. Social media literacy is considered the basis for understanding the characteristicsof new media. The aim of this research is to examine the level of social meda literacyamong local government public relations at present. Quantitative approach with surveymethod will be used in this research. The study was conducted in eight local governmentsthat have held anti-hoax declarations. The eight local governments are: Semarangregency, Semarang city, Wonosobo regency, Solo city, Banyumas regency, Bloraregency, Yogyakarta city and Province of Bali. Based on the research analysis, it can beconcluded that the managers of social media public relations of local governments whohave held anti-hoax declaration are already have enough social media literacy. The localgovernment needs to increase knowledge and skills that are technical about new mediaand social media in order to optimize the function and the role of local governmentpublic relations in the effort to ward off hoaxes. While the hardest part of social medialiteracy, which always involves the criticality literacy media, most of local governmentpublic relations have already master it. Pemeritah saat ini berusaha melawan berita-berita hoax. Salah satunya, Presiden Joko Widodo menginstruksikan untuk meningkatkan fungsi humas pemerintah dan pengelola informasi untuk menangkal hoax yang tersebar cepat di media sosial. Namun, hal itu akan berhasil jika para petugas humas pemerintah mempunyai kecakapan literasi media sosial yang memadai. Literasi media sosial dianggap sebagai dasar memahami karakteristik media baru. Penelitian ini akan melihat sejauh mana tingkat literasi media sosial di kalangan humas pemerintah daerah saat ini. Penelitian menggunakan pendekatan kuantitatif dengan metode survei. Penelitian dilakukan di delapan pemerintah daerah yang telah menggelar deklarasi anti hoax, yakni Kota Semarang, Kabupaten Semarang, Kabupaten Wonosobo, Kota Solo, Kabupaten Banyumas, Kabupaten Blora, Kota Yogyakarta, dan Provinsi Bali. Dengan tidak adanya nilai rendah, maka dapat disimpulkan bahwa para pengelola media sosial humas pemerintah daerah yang telah menggelar deklarasi anti hoax telah memiliki literasi media sosial yang cukup. Untuk mengoptimalkan fungsi dan peran humas pemerintah daerah dalam usaha menangkal hoax hanya perlu meningkatkan pengetahuan dan ketrampilan yang sifatnya teknis tentang media baru dan media sosial. Sedangkan bagian tersulit dari literasi media sosial, yaitu selalu melibatkan tingkat kekritisan para pegawai humas pemerintah daerah dalam aktifitas media sosial, telah banyak yang menguasainya.